Petrology and genesis of the Bhainskati iron ore deposit of Palpa District, western Nepal - Devkota, Sujan; Paudel, Lalu Prasad (Bulletin of the Department of Geology, 2013)
The Bhainskati Formation of the Tansen Group in the Palpa area is known for hematite iron ore deposit for long time. A prominent band of hematite of about 1-2 m thickness and extending >5 km was identified in the upper part of the Bhainskati Formation in the present study. The band is repeated three times in the area by folding and faulting. Petrographic study shows that it is oolitic ironstone of sedimentary origin. Main minerals in the band are hematite, goethite, quartz, calcite, siderite and albite. Hematite content varies considerably among samples and occurs mainly as oolite and cement. The Bhainskati ironstone with its ferrous mineral assemblage and well-rounded texture of the ooids suggests shallow marine environment (prodeltaic to estuarine) with reduced clastic input. DOI: http://dx.doi.org/10.3126/bdg.v15i0.7418 Bulletin of the Department of Geology, Vol. 15, 2012, pp. 63-68